Social cooperatives within the framework of regulatory innovations on cooperatives and the social economy in 21st century Uruguay - Reyes Lavega, Sergio (Cooperativismo & Desarrollo, 2025)
In the present work we give an account of the emergence and regulation of the “social cooperatives” type, within the particular Uruguayan framework and context of the last twenty years. The first part of the paper explores the important innovations that have occurred during the 21st century in public policies and regulations related to cooperativism and the social economy. The second part details the process that gave rise to social cooperatives, as well as their evolution, impact, and assessment.
Keywords: Social cooperatives; Regulatory innovations; Cooperativism; Social economy; public policies